PREOVULATORY CHANGES AND OVULATION IN CATTLE UNDERGOING SPONTANEOUS OR CLOPROSTENOL-INDUCED LUTEOLYSIS - BAMBANG PURWANTARA; RENE H0IER; METTE SCHMiDT; TORBEN GREVE (SEAMEO BIOTROP, 2006)
The follicular population, diameter of the ovulatory and subordinate follicles, corpus luteum (CL) size, concentration of progesterone and estradiol-17p were studied following spontaneous or cloprostenol-induced luteolysis. A total of 14 heifers received cloprostenol treatment on Day 9-11 of the cycle to synchronize their estrus. Subsequently, they were divided into two groups, one group which was allowed to undergo spontaneous luteolysis and the other group in which estrus was induced from days 9 to 12. In the induced-group, transrectal ultrasonography were performed daily started two days prior to injection until the onset of estrus. In the spontaneous-group, ultrasonography was done daily from day 15 until the onset of estrus. In both groups scanning were performed every 4 h from the onset of estrus until ovulation was ascertained. Small (SF, 2-4 mm), medium (MF.5-9 mm ) and large (LF,>9mm) size follicles were recorded. The diameter of largest and subordinate follicles were measured and blood were drawn from jugular vein at approximately around scanning and the plasma were used for measurement of progesterone (P4) and estradiol-17p (E2) concentration. There was no different in term of number of SF, MF and LF (P>0.05) between the two groups. Similarly, no effect of side (left vs. right ovary) and CL position (ipsi- vs contralateral to the ovary) was found (P>0.05). However, it was demonstrated that mean number of ovulatory follicles was higher (PO.01) in the spontaneously ovulating group while the regressing-CL size was larger in the cloprostenol induced animals (P